2012
DOI: 10.4236/as.2012.32032
|View full text |Cite
|
Sign up to set email alerts
|

Water requirements and single and dual crop coefficients of sugarcane grown in a tropical region, Brazil

Abstract: A field experiment was conducted throughout 2009/2010 in a sugarcane field of a commercial distillery located on the coastal area of Paraiba state, Brazil. The objectives were to determine sugarcane water requirements and to test the single and dual crop coefficients by comparing the calculated values of <i>ET</i> with measured ones. Crop evapotranspiration was determined by field water balance, reference evapotranspiration (<i>ET<sub>o</sub></i>) by the Penman-Monteith appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
(28 reference statements)
3
4
0
1
Order By: Relevance
“…There were only two upper (Kc > 1.15) and lower (Kc < 0.93) outliers based on the analyzed sample size. However, these values are within the Kc range observed in several studies (Inman-Bamber and McGlinchey 2003;Marin et al 2008Marin et al , 2016Marin et al , 2020Silva et al 2012;da Silva et al 2013). The Kc_mid in the ThM model retrieved from optimization was equal to 1.05 (only 3% less than the Kc obtained experimentally), whereas the adjusted Kc FAO56…”
Section: Crop Coefficient -Single and Dual Kcsupporting
confidence: 82%
See 1 more Smart Citation
“…There were only two upper (Kc > 1.15) and lower (Kc < 0.93) outliers based on the analyzed sample size. However, these values are within the Kc range observed in several studies (Inman-Bamber and McGlinchey 2003;Marin et al 2008Marin et al , 2016Marin et al , 2020Silva et al 2012;da Silva et al 2013). The Kc_mid in the ThM model retrieved from optimization was equal to 1.05 (only 3% less than the Kc obtained experimentally), whereas the adjusted Kc FAO56…”
Section: Crop Coefficient -Single and Dual Kcsupporting
confidence: 82%
“…Parameters like Kc and Kcb are available in FAO-56 for several crops or groups of crops for each growth stage, as well as an equation to adjust these parameters to local climate conditions. However, some authors have found different Kc values from those obtained by the adjusting equations, leading to inaccurate ETa estimates (Silva et al 2012;Bastidas-Obando et al 2017;Marin et al 2020). Thereby, in some cases, these values need to be determined experimentally to attain more accurate estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 11 and 12). Similar trend of K cb and its correlation with LAI were also reported for other crops 3,[22][23][24] . Such relationship would facilitate extrapolation of the results pertaining to the estimation of K cb from LAI for other regions having similar climatic conditions.…”
Section: Comparison Of Estimated Regional K C With Fao Reported Valuesupporting
confidence: 67%
“…2 and 3). While these evaporative spikes for ET o -K cb are small during this growth stage, they have been verified through studies using water balance methods (da Silva et al, 2012), lysimetry (López-Urrea et al, 2012), energy balance (Anderson et al, 2017), and isotope tracing (Nay-Htoon, 2016); thus, they should be properly simulated by cropping system models. The new ET o -K cb method is very responsive to frequent irrigations, with both the evaporation and resulting ET being highly dynamic (figs.…”
Section: Discussionmentioning
confidence: 99%